Micromachismo: the invisibility of psychological violence against women - Clayse Luciane de LimaVieira; Javan Sami Araújo dos Santos; Lúcio Luiz Izidro da Silva (Universidade Estadual de Alagoas, 2021)
This summary deals with the invisibility of psychological violence against women in the field of gender violence and consequent silencing. Attempting for the forms of abuseof patriarchal power, as well as for the machismo that permeates society, not only masculine but also not imaginary of feminine collective life. From a quali-quanti nature, we will start from a bibliographic study, a documentary and content analysis, as well as methodological approaches and other techniques for data collection. Many studies with countless faces of the defense of violence against Mulher FERNANDES (2012); SILVA (2009); ZIZEK (2008). In this sense, it is worth mentioning that this work raisedimportant questions. Taking into account, mainly, or fate of these (psychological) violences will occur in a sad way, so that many women are not perceived as inserted in a context of violence. Concerning the techniques and instruments of data collection, we even verified that the investigation contributed to the analysis and understanding of the interfaces of violence against a woman in the municipality of Maceió-AL, once the reports of the Secretary of State for Public Security ( SSP-AL) will show every 141 (cento e quarenta e um) cases of violence against women in the 2020 carnival period, in Alagoas.